High burden of mental illness and low utilization of care among school-going youth in Central Haiti: A window into the youth mental health treatment gap in a low-income country. (May 2017) - Eustache, Eddy; Gerbasi, Margaret E; Smith Fawzi, Mary C; Fils-Aimé, J Reginald; Severe, Jennifer; Raviola, Giuseppe J; Legha, Rupinder; Darghouth, Sarah; Grelotti, David J; Thérosmé, Tatiana; Pierre, Ermaze L; Affricot, Emmeline; et al.
Background: The mental health treatment gap for youth in low- and middle-income countries (LMICs) is substantial; strategies for redress are urgently needed to mitigate the serious health and social consequences of untreated mental illness in youth. Aims: To estimate the burden of major depressive episode (MDE) and posttraumatic stress disorder (PTSD) as well as utilization of care among Haitian youth in order to describe the mental health treatment gap in a LMIC setting. Methods: We estimated the point prevalence of MDE, PTSD, and subthreshold variants in a school-based sample of youth ( n  = 120, ages 18–22 years) using a modified Structured Clinical Interview for DSM-IV-TR Axis I Disorders (SCID)-based interview and examined treatment utilization among those receiving one of these diagnoses. We assessed additional psychopathology with self-report measures to examine validity of study diagnostic assignments. Results: The combined prevalence of full-syndrome or subthreshold MDE or PTSD was high (36.7%). A large majority of affected individuals (88.6%) had accessed no mental health services in the health sector, and 36.4% had accessed no care of any kind in either the health or folk sectors in the past year. Conclusion: Findings demonstrate a high mental health burden among Haiti's youth and that many youth with MDE and PTSD are not accessing mental health care.